Peningkatan Motivasi Kerja Karyawan melalui Gaya Kepemimpinan pada Bimbingan dan Konsultasi Belajar Nurul Fikri Ragunan Jakarta Selatan - wiwik widiyanti; Isnurrini Hidayat Susilowati; Julia Retnowulan; Iman Wahyudi (Universitas Bina Sarana Informatika, 2019)
The activity of a company requires quality human resources. Humans are a resource factor that is different from other resources because humans are creatures that have strong feelings and desires. Therefore, human resources must be able to be fostered and managed effectively and efficiently in order to provide optimal results for the company. Relationship patterns that occur between superiors and employees are strongly influenced by leadership style, is one of the factors that influence the behavior of others to work and strive to achieve company goals, because the success of an organization is very dependent on the effectiveness of the company. This study aims to determine the effect of leadership style on employee work motivation Guidance and Learning Consultation Nurul Fikri Ragunan. In this study, the number of respondents was 40 employees. Data was collected using a questionnaire with data analysis using a normality test, linearity test, simple regression analysis, t-test, correlation coefficient, and coefficient of determination. The results of the study showed leadership style towards employee work motivation Guidance and Learning Consultation Nurul Fikri Ragunan. The magnitude of the correlation coefficient shows the amount of 0.754, it means that the relationship between organizational culture and employee performance is quite strong. The coefficient of determination or R Squared = 0.568 which means that the organizational culture has a contribution to employee performance by 43.2% while the rest is influenced by factors other than leadership styleKeywords: Leadership Style, Motivation of Employee Work